2013
DOI: 10.1021/ic401161d
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure, Phase Transitions, and Magnetic Properties of Iridium Perovskites Sr2MIrO6 (M = Ni, Zn)

Abstract: Double perovskites containing Ir 6+ /Ir 5+ with formula Sr 2 MIrO 6 (M = Ni, Zn) have been synthesized under high oxygen pressure conditions. Their crystal structures have been studied by X-ray and neutron powder diffraction at room temperature (RT) and 2 K. At RT, these oxides crystallize in the monoclinic space group P2 1 /n with unit-cell parameters a ≈ √2a 0 , b ≈ √2a 0 , and c ≈ 2a 0 , and β ≈ 90°. The thermal evolution of the structure of the Ni-containing compound shows the presence of two phase transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 43 publications
5
74
0
1
Order By: Relevance
“…These paramagnetic centers could be defects in the sample stemming from oxygen vacancies, chemical disorder (Y/Ir site mixing), off-stoichiometry, etc. A possible scenario could be the presence of Ir 4+ or Ir 6+ ions created by intermixing and/or off-stoichiometry [35,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…These paramagnetic centers could be defects in the sample stemming from oxygen vacancies, chemical disorder (Y/Ir site mixing), off-stoichiometry, etc. A possible scenario could be the presence of Ir 4+ or Ir 6+ ions created by intermixing and/or off-stoichiometry [35,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, three different groups of XANES spectra can be distinguished at the L 3 edge in relation to the electronic state of Ir in Fig. 6 [32][33][34] In addition, we note that the occupation of the 5d orbitals may deviate from the nominal, integral valence occupation due to hybridization and band effects. For example, band-structure calculations yield n h = 5.37 for the number of holes in the related compound Sr 2 CoIrO 6 , a 11% deviation from the nominal 5d 4 configuration of Ir 5+ states.…”
Section: B Macroscopic Magnetizationmentioning
confidence: 89%
“…A detailed NPD structural study can be found elsewhere. [32][33][34] For the ordered phases, the structure was described in a monoclinic unit-cell, either I2/m (no. 12) or P2 1 /n (no.…”
Section: A Structural Characterizationmentioning
confidence: 99%
“…Another possibility for the presence of Ir ions, µ ef f is reported to be more than 3 µ B /Ir [35]. Hence, the presence of a small amount of Ir…”
Section: Magnetizationmentioning
confidence: 99%